2D Covalent Organic Frameworks Toward Efficient Photocatalytic Hydrogen Evolution. Issue 15 (22nd June 2022) - Li, Yang; Song, Xiaoyu; Zhang, Guang; Wang, Lei; Liu, Yi; Chen, Weihua; Chen, Long
Abstract: Efficiently producing clean energy is of great importance for sustainable development of the environment. Solar‐driven water splitting for H2 evolution has an important role among the renewable energy technologies. Developing high‐performance and cost‐effective photocatalysts is still a critical task before practical application. 2D Covalent organic frameworks (COFs) as photocatalysts have recently attracted widespread interest thanks to their tunable optical bandgaps, tailor‐made functionality, excellent crystallinity, high specific surface area, and good photo‐ and chemical stability. This Review focuses on the representative progress and remaining challenges in 2D COF‐based photocatalysts for hydrogen evolution. Abstract : COF it up : Covalent organic frameworks (COFs) with long‐range ordering and tunable bandgaps can be pre‐designed and become an excellent design platform for efficient photocatalysts. This Review discusses the relationship between photocatalytic performance and structure pertaining to varied linkages and provides an outlook on the challenges and future prospects on 2D COF‐based photocatalysts.